Private law framework for blockchain - Kiskis, Mindaugas (Frontiers in Blockchain, 2024)
Current attempts to regulate blockchain technology are mainly based on narrow securities law framework. Securities law classifies crypto tokens and digital assets as either securities or currency, or derivatives thereof. Such classification fails to encapsulate the full scope of possible uses and applications of blockchain technology, potentially constraining innovation. Already in 2017-2018 there were attempts to define certain rights realized through blockchain technology outside of securities law framework, however these were designed as a workaround of the securities laws, rather that comprehensive approach. The limitation of the securities law approach lies in its inability to accommodate the diverse legal rights, obligations and assets that blockchain technology can virtually reproduce. Given that securities law was never intended to address such a vast subject matter, its application risks unduly restricting digital asset commerce based on laissez-faire principles. A comprehensive legal framework for blockchain should permit private law regulation among private parties, culminating in a combined public and private law regime akin to the regulation of traditional rights, obligations and assets.